Investigating Social Media Addiction among University Students - Cakir, Veli Ozan; Ilk, Cagri; Guler, Cemal (European Scientific Journal, ESJ, 2023)
This study aimed to investigate the level of social media addiction among university students. The sample group comprised a total of 238 participants, 56.7% of whom are female and 43.3% of whom are male, enrolled at Istanbul University-Cerrahpasa Faculty of Sports Sciences. The data were collected using a personal information form and the 5-point Likert type â€œSocial Media Addiction Scaleâ€ developed by Tutgun-Ãœnal and Deniz (2015), including 41 items and four sub-dimensions. Descriptive statistical methods, including percentage and frequency, were employed in the data analysis. The Kolmogorov-Smirnov test was carried out to check whether the data were normally distributed, suggesting a normal distribution. Independent sample t-test for bivariate data and one-way ANOVA test for more than two variables were also performed. The research findings indicated a significant difference between the "Occupation" sub-dimension based on the age of the participants, while no significant difference was observed between gender, grade level, and the level of daily social media use. Consequently, social media addiction levels varied based on participantsâ€™ socio-demographic characteristics.